Interactive Multimedia as a Practicum Media for Acid-Basa Titration for Science Students Institute of Islamic Studies Sunan Doe - Urwatil Wutsqo Amry (Cigarskruie: Journal of Educational and Islamic Research, 2024)
As a newly established institution, the Sunan Doe Institute still faces various limitations, one of which is the laboratory of the Tarbiyah and Tadris Faculty. The absence of this laboratory has a significant impact on the skills and experience of the practicum of science students, especially in the chemical and science study programs. Chemistry is a branch of science that studies concepts at the macroscopic, submicroscopic, and symbolic levels, so that chemistry learning really requires supporting facilities in the form of laboratories. One material that demands understanding at the three levels is the concept of acid-base titration. With the unavailability of laboratories within the Sunan Doe Institute, lecturers are required to provide alternative learning media that are able to provide virtual practicum experience. One solution that can be used is interactive multimedia, which is able to simulate practicum activities and encourage active student participation. This study uses a 4D development model developed by Thiagarajan. The results of product validation by material experts show a percentage of feasibility of 90.80% with valid categories without revision. Assessment by media experts obtained a value of 96.19% with the valid category and did not require revision. Small group trials produce a score of 90.78%, also in the valid category and do not need to revise. Based on these results, the interactive multimedia of the acid-base titration developed is declared valid and suitable for use in learning activities.